Identification and differentiation of gluteus medius tendon pathology using ultrasound and magnetic resonance imaging. (June 2019) - Docking, Sean Iain; Cook, Jill; Chen, Stephanie; Scarvell, Jennie; Cormick, Wes; Smith, Paul; Fearon, Angela
Abstract: Background: It has been suggested that imaging findings play a role in directing treatment for Greater Trochanteric Pain Syndrome. Structural diagnoses associated with Greater Trochanter Pain Syndrome include gluteal tendinosis, and partial- or full-thickness gluteal tendon tears. However, few studies have compared imaging to confirmed tendon pathology observed during surgery. Objective: To investigate the ability of magnetic resonance and ultrasound imaging to identify the presence of a pathological gluteus medius tendon in comparison to surgical and histological findings. Study design: Cross-sectional study. Methods: 26 participants undergoing gluteal tendon reconstruction surgery or hip arthroplasty were included. Prior to surgery, participants underwent both magnetic resonance (MR) (n = 23) and ultrasound (US) (n = 25) imaging. A radiologist (MR) and nuclear physicians (US) classified the gluteus medius tendon as normal, tendinosis (no tear), partial-thickness tear, or full-thickness tear. Results: Ultrasound identified 17 out of the 19 pathological gluteus medius tendons correctly. However, 5 of the 6 normal tendons were incorrectly identified as exhibiting pathology on ultrasound. Magnetic resonance rated 11 out of 17 pathological tendons as abnormal, with 4 out of 6 normal tendons identified correctly. Both imaging modalities were poor at identifying and differentiating between tendinosis and partial-thickness tears. Conclusion: Both imaging modalities showed a reasonable ability to identify tendon pathology. While limited by sample size, these early findings suggest that both imaging modalities may be limited in identifying specific pathoanatomical diagnoses, such as partial-thickness tears. These limitations may misdirect treatment. Highlights: MR and US adequate in differentiating between normal and abnormal tendon. Imaging limited in identifying a torn tendon. Clear, concise guidelines needed for identification of specific imaging diagnoses.